Bielefeld may in fact not exist - Empirical evidence from official population data - Patrick Winter (Journal of Economics and Statistics, 2023)
The “Bielefeld conspiracy” has long disputed the existence of Bielefeld, a (supposed) German city. In this paper, an approach is developed to test such a theory empirically by auditing officially reported population numbers, arguing that real cities would not fake these. It is shown that Bielefeld's data, in fact, violate the Benford law, a statistical law that they should follow if they were genuine. This anomaly is found only for Bielefeld, in contrast to all other tested similar and dissimilar cities, across two decades, and with highest significance by five statistical tests. The Bielefeld conspiracy remains as the most or even only plausible explanation for these findings.
Keywords: H83; C46; 330; Benford law; Bielefeld conspiracy; population data